Novel Natural Allelic Variations at the Rht‐1 Loci in Wheat. Issue 11 (November 2013) - Li, Aixia; Yang, Wenlong; Lou, Xueyuan; Liu, Dongcheng; Sun, Jiazhu; Guo, Xiaoli; Wang, Jing; Li, Yiwen; Zhan, Kehui; Ling, Hong‐Qing; Zhang, Aimin
Abstract: Plant height is an important agronomic trait. Dramatic increase in wheat yield during the "green revolution" is mainly due to the widespread utilization of the Reduced height ( Rht ) ‐1 gene. We analyzed the natural allelic variations of three homoeologous loci Rht‐A1, Rht‐B1, and Rht‐D1 in Chinese wheat ( Triticum aestivum L.) micro‐core collections and the Rht‐B1 / D1 genotypes in over 1, 500 bred cultivars and germplasms using a modified EcoTILLING. We identified six new Rht‐A1 allelic variations ( Rht‐A1b–g ), eight new Rht‐B1 allelic variations ( Rht‐B1h–o ), and six new Rht‐D1 allelic variations ( Rht‐D1e–j ). These allelic variations contain single nucleotide polymorphisms (SNPs) or small insertions and deletions in the coding or uncoding regions, involving two frame‐shift mutations and 15 missenses. Of which, Rht‐D1e and Rht‐D1h resulted in the loss of interactions of GID1‐DELLA‐GID2, Rht‐B1i could increase plant height. We found that the Rht‐B1h contains the same SNPs and 197 bp fragment insertion as reported in Rht‐B1c . Further detection of Rht‐B1h in Tibet wheat germplasms and wheat relatives indicated that Rht‐B1c may originate from Rht‐B1h . These results suggest rich genetic diversity at the Rht‐1 loci and provide new resources for wheat breeding.